2009
DOI: 10.1111/j.1865-1682.2009.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Bluetongue Virus Detection by Real-Time RT-PCR inCulicoidesCaptured During the 2006 Epizootic in Belgium and Development of an Internal Control

Abstract: After the emergence of bluetongue (BT) in Belgium in 2006, two types of entomological surveys were initiated, the one to identify the local vector species, and the other to study their population dynamics. In the vector study, Culicoides were captured near farms with recently infected cattle or sheep; in the population study Culicoides were captured in two meadows situated in the BT-affected region. A total of 130 pools of parous, non-blood engorged female midges (with a mean of 7.5 midges per pool) were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 31 publications
1
36
0
1
Order By: Relevance
“…The first, carried out in Belgium and utilizing small pools of pigmented Culicoides (<10 individuals/pool) recorded a C q range of 35.8–42.8 when utilising a cut-off value of 45 [19]. From the current study it appears likely that these ‘positive’ pools either contained no Culicoides with fully disseminated infections or that BTV RNA levels were reduced substantially during processing.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The first, carried out in Belgium and utilizing small pools of pigmented Culicoides (<10 individuals/pool) recorded a C q range of 35.8–42.8 when utilising a cut-off value of 45 [19]. From the current study it appears likely that these ‘positive’ pools either contained no Culicoides with fully disseminated infections or that BTV RNA levels were reduced substantially during processing.…”
Section: Discussionmentioning
confidence: 64%
“…‘Positive’ findings of detected viral RNA may merely have represented inactivated BTV that had persisted in individual Culicoides following an infected blood meal, or a sub-transmissible infection such as commonly occurs in this genus [4]. Subsequent to these early studies, the inclusion of cycle threshold (C q ) values as a semi-quantitative indication of RNA concentration has become more common [18], [19]. Uncertainty remains, however, in interpretation of semi-quantitative or sqPCR data from pools of Culicoides and in the relationship between C q values representing quantity of viral RNA and the quantity of infectious virus as a means of defining transmissible infections.…”
Section: Introductionmentioning
confidence: 99%
“…chiopterus (Meigen, 1830); C. ( A. ) imicola Kieffer, 1913; C. ( Culicoides ) pulicaris (L.); and C. ( C. ) lupicaris Downes & Kettle, 1952 [210]. Within the subgenus Culicoides , C. ( C .)…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge in interpreting arbovirus cycle threshold (C q ) values derived by sqPCR from pools of Culicoides lies in the fact that sub-transmissible infections are common in Culicoides occurring most frequently during initial infection and release from the hind mid-gut [15], [16]. This renders the numerous studies where only small numbers of positive pools of Culicoides are reported difficult to interpret [17], [18], [19], [20], [21], [22], although comparison with predicted quantities of virus in the original blood meal in larger studies can be used to demonstrate that at least limited replication of virus has occurred in the putative vector and that wide-scale infection of Culicoides did occur [23].…”
Section: Introductionmentioning
confidence: 99%